2004
DOI: 10.1136/bmj.328.7440.607
|View full text |Cite
|
Sign up to set email alerts
|

Use of hospitals, physician visits, and hospice care during last six months of life among cohorts loyal to highly respected hospitals in the United States

Abstract: Objective To evaluate the use of healthcare resources during the last six months of life among patients of US hospitals with strong reputations for high quality care in managing chronic illness. Design Retrospective cohort study based on claims data from the US Medicare programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
191
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(201 citation statements)
references
References 18 publications
8
191
0
2
Order By: Relevance
“…Future efforts to understand these demographic differences in hospice use should focus on patients with other cancers. Similar to other studies, 9,10,19,20,22 we found that women living in urban areas were more likely than women in rural areas to enroll in hospice, and we found significant variation by geographic area. Focused efforts to understand how patients, physicians, and hospices interact at the local level may be important to understand better the reasons for these area-level variations; our study suggests that future studies must also consider patients' interactions with physicians and hospitals.…”
Section: Discussionsupporting
confidence: 79%
“…Future efforts to understand these demographic differences in hospice use should focus on patients with other cancers. Similar to other studies, 9,10,19,20,22 we found that women living in urban areas were more likely than women in rural areas to enroll in hospice, and we found significant variation by geographic area. Focused efforts to understand how patients, physicians, and hospices interact at the local level may be important to understand better the reasons for these area-level variations; our study suggests that future studies must also consider patients' interactions with physicians and hospitals.…”
Section: Discussionsupporting
confidence: 79%
“…Such undesired variability may decrease system reliability (introducing avoidable opportunity for error), 26 and lead to under-use of needed therapies as well as overuse of unnecessary therapies. 1 Our work extends prior research that has identified wide variation in patterns of hospital admission, use of hospital resources, and processes of inpatient care, [27][28][29][30][31][32] by documenting reported variation in the use of common inpatient therapies. Rates of hospital admission may vary by as much as 7-fold across regions.…”
Section: Discussionsupporting
confidence: 62%
“…48 We derived and externally validated our model at two tertiary-care medical centers in New York City, where utilization of acute care in the last 6 months of life is greater than at other major medical centers in the United States. 49 Our model still needs to be validated in community hospitals and in other geographic regions where case mix and patient care may differ.…”
Section: Discussionmentioning
confidence: 99%